Hepatoprotective Effects of Vernonia amygdalina (Astereaceae) Extract on CCl4-Induced Liver Injury in Broiler Chickens - Tokofai, Bemela Mawulom; Idoh, Kokou; Oke, Oyegunle Emmanuel (MDPI, 2021)
The aim of this study was to evaluate the effect of Vernonia amygdalina leaf extract (VALE) on the carbon tetrachloride-induced hepatotoxicity (CCl4) in broiler chickens. A total of 360-day-old broilers were divided into 4 treatments of 90 birds each consisting of 6 replicates of 15 birds each. The treatments were birds offered 1 mL/kg BW saline (control group), 100 mg/kg BW VALE, 1 mL/kg BW CCl4 (CCl4-treated group), and 100 mg/kg BW VALE + 1 mL/kg BW CCl4 (VALE + CCl4 group). Blood samples were collected at 42 days of age and analyzed for the liver enzymes: alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), and selected biochemical parameters. The experiment was laid out in a completely randomized design. The results obtained showed that VALE had the potential to mitigate the adverse effects of CCl4 on protein and lipid metabolism as reflected in the low serum malondialdehyde (MDA) levels, which is a marker of lipid peroxidation. The aqueous extract of Vernonia amygdalina (VA) at a dose of 100 mg/kg body weight showed a moderate hepatoprotective effect by reducing serum AST levels (p < 0.05). The levels of serum AST, ALP, ALT, and GGT were significantly increased in CCl4- treated birds compared to the control group, reflecting carbon tetrachloride-induced liver damage. The VALE + CCl4 group showed a significantly higher amount of ALP compared to birds treated with carbon tetrachloride, suggesting a hepatoprotective effect. To conclude, Vernonia amygdalina aqueous extract can be used to confer protection against hepatotoxicity, which can induce severe hepatocellular damage in birds.
Animals 2021, 11, 3371, pg 1-11
Keywords: Vernonia amygdalina; CCl4; oxidative stress; hepatoprotection; broilers; Amegnona Agbonon; University of Lomé; Togo; CERSA